Analysis, design and construction of steel space frames - Ramaswamy, G. S., 1923- (Thomas Telford, 2002)
This is the first in-depth book to present all instances and applications of space frames in various engineering schemes. It uses case studies and numerous illustrations to examine steel space frames from their design to their structural engineering performance.
Keywords: Space frame structures -- Design and construction.; Space frame structures.; Steel framing (Building) -- Design and construction.; elektronické knihy; electronic books